Unimas, Utsunomiya University carry out e-EduTour2021 - Rethinasamy, Soubakeavathi; Damien, Mikeng; Hussien, Nurul Huzaimah; Abang Ahmad, Dayang Hartijah; Rosli, Liyana; Yusuf, Keezrawati Mujan; Joseph, Ramanair (Sarawak Tribune, 2021)
KUCHING: Universiti Malaysia Sarawak (Unimas) and its strategic partner Utsunomiya University Japan (UU) have carried out their student mobility programme virtually.